17. Haukebø 2: Boplass fra senmesolitikum - Cerbing, Mikael; Kvalheim, Alice Sunde (Tromura, 2025)
Haukebø 2 was a small, partially disturbed site, dated to the Late Mesolithic. At the site, a cleared activity area with a possible hearth and tent ring was identified, along with more general, scattered activity.Haukebø 2 was situated in an unusual location, almost hidden on the backside of a small elevation at the southern entrance to Gausvik Bay. In addition to the activity area, a few possible uprights, a larger number of fishing sinkers, and a small but varied assemblage of lithic tools, primarily in flint, were recorded.
Keywords: Archaeological excavation; Late Mesolithic; Early stone age; Fishing sinkers; Tent